Anthraquinones as Photoredox Catalysts for the Reductive Activation of Aryl Halides. Issue 1 (20th December 2017) - Bardagi, Javier I.; Ghosh, Indrajit; Schmalzbauer, Matthias; Ghosh, Tamal; König, Burkhard
Abstract : Quinones are ubiquitous in nature as structural motifs in natural products and redox mediators in biological electron‐transfer processes. Although their oxidation properties have already been used widely in chemical and photochemical reactions, the applications of quinones in reductive photoredox catalysis are less explored. We report the visible‐light photoreduction of aryl halides (Ar–X; X = Cl, Br, I) by 1, 8‐dihydroxyanthraquinone. The resulting aryl radical anions fragment into halide anions and aryl radicals, which react through hydrogen abstraction or C–C bond‐forming reactions. The active photocatalyst is generated from 1, 8‐dihydroxyanthraquinone by photoinduced single‐electron reduction to the radical anion or subsequent protonation and further reduction (or vice versa) to the semiquinone anion. Subsequent visible‐light excitation of the anthraquinone radical anion or semiquinone anion converts them into very potent single‐electron donors. A plausible mechanism for the reaction is proposed on the basis of control experiments and spectroscopic investigations. Abstract : Anthraquinone derivatives of synthetic or natural origin form radical and semiquinone anions through visible‐light photoinduced electron‐transfer (PET) processes. The subsequent excitation of the colored radical or semiquinone anion of 1, 8‐dihydroxyanthraquinone accumulates enough energy for the activation of the carbon–halogen bonds of (hetero)aryl halides.